1999
DOI: 10.1590/s0102-311x1999000100003
|View full text |Cite
|
Sign up to set email alerts
|

Desigualdade de renda e situação de saúde: o caso do Rio de Janeiro

Abstract: This ecological analysis addresses the association between income inequality and health status in the municipality of Rio de

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
43

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 21 publications
1
18
0
43
Order By: Relevance
“…Szwarcwald et al 14 state that, several studies have reported, in a consistent manner, the existence of better health conditions in societies with a more equitable distribution of income. In addition, some societies have much better health conditions than would be expected for their levels of income and vice versa.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Szwarcwald et al 14 state that, several studies have reported, in a consistent manner, the existence of better health conditions in societies with a more equitable distribution of income. In addition, some societies have much better health conditions than would be expected for their levels of income and vice versa.…”
Section: Discussionmentioning
confidence: 81%
“…Some districts are geographically extensive, inhabited by large populations, which may not be socially and economically homogeneous. For this reason, some authors 14 have suggested that indicators of inequality with respect to income, such as the Gini Index and/or the income ratio of the poorest and the richest be employed instead of absolute income in this type of analysis. Thus, it would be useful, if such data were available, to utilize data concerning indicators of inequality for districts of the Municipality of Sao Paulo.…”
Section: Discussionmentioning
confidence: 99%
“…18 Portanto, a afirmação sobre a "inexistência de qualquer associação entre as taxas de mortalidade por homicídios e pobreza ou migração" 21 merece ser relativizada à luz dos resultados da presente investigação e de outros estudos brasileiros. 1,4 Pesquisa realizada em Recife (Lima & Ximenes, 8 1998), por exemplo, ainda que apresente resultados que contrariem a idéia segundo a qual o crescimento das cidades, juntamente com a migração das populações rurais e o aumento da pobreza, seria responsável pelo crescimento da violência, motivou os seus autores a chamarem a atenção para o fato de que a acentuação das desigualdades nas condições de vida pode estar contribuindo para o aumento da violência como um todo e em especial em relação aos homicídios".…”
Section: Discussionunclassified
“…9 As estatísticas oficiais, divulgadas de forma agregada e descrevendo as populações como se fossem homogê-neas, deixam de evidenciar as distribuições espaciais diferenciadas da mortalidade por causas externas. Essa heterogeneidade, no entanto, tem sido apontada por investigações 8,16 que analisam relações com variáveis socioeconômicas como renda, educação, consumo de bens e serviços, que tendem a assumir um papel relevante na determinação de desigualdades em saúde, 18 especialmente no que se refere aos homicídios. 1 A mortalidade por essa última causa apresenta algumas particularidades em relação a sua distribuição por sexo, idade, raça, condições socioeconômicas e regiões geográ-ficas.…”
Section: Introductionunclassified
“…For Prata 4 , the concept of inequality refers to the relationship between development and social justice and, therefore, relates to the inequity in the distribution of income, education, housing, and services (health services, piped water supply, and sanitation), in the access to jobs, consumer goods and land, and in decision making and social influence. According to Szwarcwald et al 5 , a theme widely discussed in the scientific literature, is how health differentials reflect the social inequalities of a population, manifesting as different morbidity and mortality profiles and early illness in less privileged social groups. Studies cited by the same authors show that societies with better income distribution also have better health conditions.…”
Section: Introductionmentioning
confidence: 99%